Determinan Tingkat Kepatuhan Wajib Pajak pada Badan Pendapatan Daerah Kota Palembang - Salsabila Naela Ramadhani; Sulaiman; M. Husni Mubarok (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the determinant of the level of taxpayer compliance at the Regional Revenue Board of Palembang City. This type of research is quantitative. The sample used in this study amounted to 50 Civil Servants in the Palembang City Regional Revenue Agency in the Tax section. The type of data used was primary data. The sampling technique uses a saturated sampling technique. The data in this study indicate that the variables Tax Sanctions, Moral Obligation, Quality of Service have a significant positive effect and tax audits have a negative effect on the variable taxpayer compliance